2007
DOI: 10.1007/s00244-007-9046-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Hepatic Speciation of Copper in Rainbow Trout (Oncorhynchus mykiss) During Chronic Waterborne Copper Exposure

Abstract: To protect cells from toxicity, metal-sensitive cellular compartments must be insulated against essential but toxic metals [such as copper (Cu)] accumulated in excess of metabolic requirements. We measured Cu concentrations at the organ and hepatic subcellular levels in juvenile rainbow trout (Oncorhynchus mykiss) during exposure to sublethal waterborne Cu (40 microg/L) for 21 days. There was a time-dependent accumulation of Cu in the gill, liver, plasma, and carcass, with significant difference in Cu-exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…The liver is the main organ responsible for the maintenance of copper homeostasis and is also a possible target for copper-induced damage in fish (Grosell et al 1998;Abdel-Tawwab et al 2007;Kamunde and McPhail 2008). In our study, we observed hydropic and vacuolar degeneration of hepatocytes, the dilatation of capillaries, mild hyperaemia, and cholestasis.…”
Section: Discussionsupporting
confidence: 60%
“…The liver is the main organ responsible for the maintenance of copper homeostasis and is also a possible target for copper-induced damage in fish (Grosell et al 1998;Abdel-Tawwab et al 2007;Kamunde and McPhail 2008). In our study, we observed hydropic and vacuolar degeneration of hepatocytes, the dilatation of capillaries, mild hyperaemia, and cholestasis.…”
Section: Discussionsupporting
confidence: 60%
“…The copper concentrations selected for the main experiment (1, 10 and 50 mM) took into account the cell viability results and the knowledge that fish captured at impacted sites had concentrations in plasma that reach 50 mM [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other binding sites may be involved in metal chelation in corkwing wrasse, thereby eliminating the need for MT induction. Kamunde and MacPhail (2008) found indiscriminate Cu binding in all subcellular fractions of rainbow trout liver suggesting that Cu-binding sites are ubiquitous in this organ. Also, base-line levels of MT in corkwing wrasse may be sufficient to counteract the metal exposure at this site.…”
Section: The Copper Minementioning
confidence: 92%